Production of Aluminum Matrix Composite Material by Active Carbon Additive - Eisay, Ayman M. S.; Turkyilmaz, Aydın (Springer Science and Business Media LLC, 2021)
Abstract
The effectiveness of composite materials with the addition of activated carbon produced from biomaterial with a new application on aluminum-based composite materials was investigated in this study.Activated carbon was produced from the peanut shells via the chemical activation method and the obtained activated carbon was mixed with aluminum and composite material. For the characterization of the composite material obtained, XRD and SEM-EDS optical photographs were assessed in the experimental process. According to Vickers Hardness and Dynamic Micro Hardness results, the sample with the hardness value of 2% AC added had the highest hardness value. The elastic modulus values was found to increase by 3.4 times (9.59GPa) compared to aluminum with the addition of 2% activated carbon. This increases with activated carbon quantity, and weakens the matrix structure due to weak van der waals interaction with aluminum, which reduces hardness; therefore, the best ratio of the activated carbon reinforcement to the aluminum matrix was obtained at 2% activated carbon addition.